OTHERWORLDLY LANDSCAPES IN THE HISTORIC TEXT TRUYỀN KỲ MẠN LỤC BY NGUYEN DU - Van Hoa Pham (Tạp chí Khoa học Đại học Đà Lạt)
Truyền kỳ mạn lục, the only literary work of the renowned Confucian scholar Nguyen Du, is considered the brilliant peak of Vietnamese supernatural tales. This paper aims to decode a distinctive aspect of the artistic thinking in Truyền kỳ mạn lục and contribute to establishing the applicability of landscape theory in the study of medieval literature. By applying landscape theory and model-setting methods, the paper analyzes and compares the richness and uniqueness of spatial movement types that create otherworldly landscapes as a hallmark of supernatural stories. The paper identifies the methods, nuances, artistic discourse, and construction of models of otherworldly landscapes in 20 stories from the historic text, Truyền kỳ mạn lục, highlighting both the similarities and differences in the artistic thinking of otherworldly landscapes and the unique artistic features in Nguyen Du’s creation of these landscapes. This study promotes Vietnamese literary heritage and contributes to advancing the research and teaching of the genre of East Asian supernatural literature at educational institutions.